1991
DOI: 10.1111/j.1365-2672.1991.tb04453.x
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of the polysaccharide from Propionibacterium acidi‐propionici on whey‐based media

Abstract: M. RACINE, J. DUMONT, C.P. CHAMPAGNE AND A. MORIN. 1991. The effects of lactose, ammonium and phosphate on the production of extracellular polysaccharide from Propionibacterium acidi‐propionici VM‐25 were studied in whey‐based media. The polysaccharide was composed of a water‐soluble fraction (15% w/w), a water‐insoluble fraction (27% w/w) and ca 65% (w/w) of ash. Up to 15 g/l of polysaccharide was produced during growth on partially deproteinated whey, supplemented with lactose, NH4 Cl and KH2 PO4, after incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 14 publications
3
26
0
1
Order By: Relevance
“…thermophilus and suggested that this degradation is due to an enzyme, possibly a glucohydrolase, which progressively destroys the polymer. Polymer degradation has also been reported by other investigators (28,29) in strains of L. casei and Propionibacterium acidi-propionici. Our results clearly show the presence of different glycohydrolases in cell extracts.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…thermophilus and suggested that this degradation is due to an enzyme, possibly a glucohydrolase, which progressively destroys the polymer. Polymer degradation has also been reported by other investigators (28,29) in strains of L. casei and Propionibacterium acidi-propionici. Our results clearly show the presence of different glycohydrolases in cell extracts.…”
Section: Discussionmentioning
confidence: 53%
“…Polysaccharides should therefore be considered as minor products diverted away from glycolysis rather than as secondary metabolites. It was previously found in other EPS-producing LAB that EPS biosynthesis is growth associated (9,14,18,29,34). The growth-associated biosynthesis of EPS from S. thermophilus LY03 (9) is supported by the need for an equilibrated carbon/ nitrogen ratio and by a direct relationship between optimal growth conditions (temperature, pH, and oxygen tension) and EPS yields.…”
Section: Discussionmentioning
confidence: 99%
“…shermanii), the single gene gtf encoding for a β-d-glucan synthase that is responsible for the synthesis of surface polysaccharide has been identified [40,116] and the EPS produced was also characterized. Both homopolysaccharide [116,117] and heteropolymers [118] were described and it has been reported that production of EPS by propionibacteria is a strain-dependent property (due to an IS element in the gtf promoting sequence) that is influenced by the medium composition and the fermentation conditions [119,120]. Further studies are needed to elucidate the role of these polymers and their potential applications.…”
Section: Nutraceuticals Production: Cla Vitamins Eps and Trehalosementioning
confidence: 99%
“…Different nitrogen concentrations in fermentation broths were achieved by addition of different levels of yeast extract and NH 4 NO 3 (organic and inorganic nitrogen sources) to a basal medium. Racine, et al (1991) showed that biopolymer production was enhanced when nitrogen supply was limited and the carbon source was in excess. The results presented in this study Showed that biopolymer production decreased as the nitrogen concentration increased.…”
Section: Discussionmentioning
confidence: 99%